Engineering Education System in Modern India:A Paradigm Shift - Shekhawat, Sanjay P.; Husain, Mujahid; Patil, Saroj (Journal of Engineering Education Transformations, 2019)
Technical education transforms a human being into a human resource. It enables mankind to be a resource creator. The technical education scenario in India is not at all satisfactory. The present paper investigates the lacuna in the curriculum in Indian Universities. It also proposes the means and methods of improving the curriculum to make it relevant and efficient. The present paper has proposed revolutionary changes to produce employable engineers. It is hope that the regulatory authorities will take sincere cognition of this and prepare model educational system of engineering.